Relationship between Selected Anthropometric Characteristics and Swimming Performance in Young Male and Female Swimmers - Taxtalis Θεοχάρης; Gourgoulis Βασίλειος; Koltsis Χρήστος; Toubekis Αργύρης; Aggeloussis Νικόλαος; Volaklis Κωνσταντίνος; Tokmakidis Σάββας (Inquiries in Physical Education and Sport, 2014)
The purpose of the present study was to investigate the relationship between selected anthropometric characteristics and swimming performance in young male and female swimmers and to determine the prediction possibility of the competitive performances based on selected anthropometric characteristics. The sample of the study was 93 swimmers (41 male and 52 female swimmers), who were divided into three age categories: 13, 14 and 15-16 years old. There were measured selected anthropometric characteristics (body mass, body height, body fat, segment length, thorax region, segments diameter) and the swimming performance in 100, 200, 400 and 800 m, which were common distances for both genders. For the statistical treatment of the data two-way analysis of variance, Pearson correlation and hierarchical multiple regression analysis were used. The results showed statistically significant relationships between the swimming performances and selected anthropometric characteristics, such as the body height, the length of the arm, the diameter of the shoulder, the length of the palm and the percentage of body fat. However, these correlations were not of the same magnitude for both genders and for all the age categories. Moreover, there were observed sufficient possibilities for the prediction of the swimming performances based on selected anthro-pometric characteristics, which were increased as the age of the swimmers increased, especially in male swimmers. However, it seems that for more accurate predictions of the swimming performances in the various ages, apart from the anthropometric characteristics, it should be taken into account and other pa-rameters that are decisive for the swimming performance.